Cobalt-chromium-nickel alloy powder for additive manufacturing and method for preparing and use thereof
Patent Information
- Application Number
- CN202611086420.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-30
AI Technical Summary
然而,将 ODS 技术与增材制造工艺相结合时,面临着诸多技术挑战:如何实现纳米氧化物在合金粉末中的均匀分散与牢固结合,避免在激光熔融过程中出现氧化物团聚;如何设计合金成分,使打印件既具备良好的成形性,又能在高温环境下保持优异的综合力学性能;如何优化制备工艺,在保证粉末球形度和流动性的同时,确保氧化物弥散相的均匀分布
1.本发明提供一种适用于增材制造(特别是激光粉末床熔融技术)的氧化物弥散强化合金粉末,该合金粉末不仅具有良好的球形度、高流动性及适宜的粒径分布,以确保打印过程的顺利进行,其成分设计能够在打印后形成具有均匀纳米氧化物弥散相的致密构件,更重要的是,可以用更小的成本和更短的时间改变粉末的成分。
Smart Images

Figure CN122999963A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of high-temperature structural materials for additive manufacturing, and particularly relates to cobalt-chromium-nickel alloy powder for additive manufacturing, its preparation method and application. Background Technology
[0002] In the manufacturing of high-end equipment such as aerospace and energy power, high-temperature components have long faced extremely complex service environments. They not only need to withstand temperatures exceeding 900℃, but also possess excellent strength, plasticity, and creep resistance to ensure the reliability and service life of the equipment. While traditional high-temperature alloys meet basic high-temperature requirements to a certain extent, their inherent performance shortcomings are becoming increasingly apparent as modern industry demands higher equipment performance. On the one hand, conventional high-temperature alloys exhibit significant strength degradation and insufficient creep resistance at high temperatures, making them unsuitable for the long-term service requirements of critical components such as turbine blades for aero-engines and heat-resistant components for energy equipment. On the other hand, the composition design and manufacturing processes of traditional alloys often fail to balance comprehensive mechanical properties at both room and high temperatures. Some alloys, while maintaining good strength at room temperature, experience a sharp decline in plasticity at high temperatures, or vice versa, failing to achieve synergistic optimization of strength and plasticity.
[0003] Additive manufacturing technology (especially laser powder bed fusion) has emerged as a rapidly developing advanced manufacturing process in recent years, offering new solutions for the manufacture of high-temperature components due to its advantages such as high precision and strong ability to form complex structures. However, additive manufacturing places extremely stringent requirements on the performance of alloy powders. Not only must the powder possess good sphericity, high flowability, and suitable particle size distribution to ensure the stability of the printing process and the quality of the formed parts, but more importantly, the powder composition design must be adapted to the process characteristics of additive manufacturing to avoid problems such as component segregation and oxide agglomeration during printing. Existing high-temperature alloy powders suitable for additive manufacturing either lack effective strengthening mechanisms, resulting in insufficient high-temperature mechanical properties, or suffer from uneven oxide dispersion and weak bonding with the metal matrix, making it difficult to guarantee the performance consistency and reliability of the final printed parts. For example, in the additive manufacturing process, some alloy powders are prone to agglomeration or segregation of nano-oxides, failing to form a uniform dispersion strengthening effect, resulting in a significant decrease in the strength and creep resistance of the parts at high temperatures. Other powders, while possessing certain high-temperature performance, suffer from poor sphericity and flowability, easily leading to problems such as powder clogging and uneven powder distribution during printing, affecting the density and mechanical property stability of the formed parts. Furthermore... Oxide dispersion strengthening (ODS) technology introduces uniformly distributed nanoscale oxide particles into a metal matrix. Utilizing the pinning effect of these oxide particles on dislocation movement and grain boundary migration, it can significantly improve the high-temperature strength, creep resistance, and thermal stability of alloys, making it an effective way to address performance bottlenecks in high-temperature components. However, combining ODS technology with additive manufacturing processes faces numerous technical challenges: how to achieve uniform dispersion and firm bonding of nanoscale oxides in alloy powders, avoiding oxide agglomeration during laser melting; how to design alloy compositions that ensure both good formability and excellent comprehensive mechanical properties at high temperatures; and how to optimize the fabrication process to guarantee the uniform distribution of the oxide dispersion phase while maintaining powder sphericity and flowability. Currently, existing oxide dispersion strengthened alloy powders often suffer from unreasonable element ratios and a single strengthening mechanism in their composition design. Furthermore, the fabrication processes struggle to achieve uniform coating of nanoscale oxides, limiting their application in additive manufacturing and failing to meet the stringent requirements of high-end high-temperature components in aerospace, energy, and other fields.
[0004] Therefore, developing a novel oxide dispersion-strengthened alloy powder suitable for additive manufacturing (especially laser powder bed melting technology) that combines good formability and excellent high-temperature mechanical properties, while providing a preparation method that can achieve uniform coating of nano-oxides, and high-performance printed parts made from this powder, is of great practical significance and application value for breaking through the manufacturing bottleneck of high-end high-temperature components and promoting technological progress in aerospace, energy and power fields. Summary of the Invention
[0005] In view of this, the present invention discloses a cobalt-chromium-nickel alloy powder for additive manufacturing, its preparation method and application.
[0006] The present invention adopts the following technical solution: A cobalt-chromium-nickel alloy powder for additive manufacturing, the alloy powder being composed of pre-alloyed powder, elemental metallic powder, and oxide powder, wherein the elemental composition of the alloy powder is Co. a Cr b Ni c Mo d W e Re f Al g C h (RE2O3) iThe alloy powder contains rare earth elements (RE) and oxide powder (RE2O3). The mass percentages of each element or component in the alloy powder are as follows: 10 ≤ a ≤ 50 wt%, 10 < b ≤ 50 wt%, 10 < c ≤ 50 wt%, 0 < d ≤ 5 wt%, 0 < e ≤ 5 wt%, 0 < f ≤ 5 wt%, 0 < g ≤ 2 wt%, 0 < h ≤ 2 wt%, 0 < i ≤ 2 wt%, and a + b + c + d + e + f + g + h + i = 100 wt%. The metallic elemental powder is Mo elemental powder.
[0007] Furthermore, the chemical formula of the pre-alloyed powder is Co. a Cr b Ni c W e Re f Al g C h The atomic ratios of the components in the formula are: 10≤a≤50 at%, 10<b≤50 at%, 10<c≤50 at%, 0<e≤5 at%, 0<f≤5at%, 0<g≤2 at%, 0<h≤2 at%, and a+b+c+e+f+g+h=100 at%.
[0008] Furthermore, the particle size of the metal elemental powder is 1~5 μm.
[0009] Furthermore, the oxide powder is at least one of yttrium oxide, lanthanum oxide, cerium oxide, and neodymium oxide, and the particle size of the oxide powder is 100~200 nm.
[0010] Furthermore, the chemical formula of the pre-alloyed powder is Co. 32.7 Cr 32.2 Ni 32.3 W1Re 0.5 Al1C 0.3 .
[0011] A method for preparing the above-mentioned alloy powder, the method comprising the following steps: S1) Weigh the pre-alloyed powder raw materials according to the designed proportions, convert the atomic percentages of each component of the pre-alloyed powder raw materials into mass percentages, and weigh the raw materials according to the mass percentages. The purity of the raw materials is ≥99.9 wt.%. S2) The raw materials weighed in S1) are mixed and then subjected to vacuum induction melting to obtain alloy ingots; S3) The alloy ingot described in S2) is subjected to gas atomization treatment to obtain pre-alloyed powder; S4) The pre-alloyed powder described in S3) is sieved to obtain pre-alloyed powder with a size of 15~53 μm; S5) According to the designed ratio, weigh the required mass of elemental metal powder, oxide powder and the pre-alloyed powder obtained in S4), and perform drying treatment; S6) Subject the dried elemental metal powder, oxide powder and pre-alloyed powder to resonant powder mixing treatment, to obtain the alloy powder suitable for additive manufacturing.
[0012] Further, the specific process of the vacuum induction melting includes: placing the raw materials in a crucible, pumping the melting chamber to a low vacuum, supplying power at low power to preheat the furnace charge, then pumping the melting chamber to a high vacuum, supplying power at high power to maintain the melting temperature at 1550~1600°C, applying electromagnetic stirring to promote composition homogenization, and performing pouring after uniform stirring.
[0013] Further, the specific process of the gas atomization treatment includes: heating the alloy ingot to a molten state under the protection of an argon atmosphere, obtaining fine droplets through a supersonic argon flow nozzle, with an atomization pressure of 3~9 MPa. The atomized droplets shrink into spheres under the action of surface tension during the falling process in the atomization tower, and are rapidly cooled and solidified into solid pre-alloyed powder.
[0014] Further, the specific process of the resonant powder mixing treatment includes: placing the elemental metal powder, oxide powder and pre-alloyed powder into the matching container of the powder mixer, wherein the powder filling ratio in the container shall reach 80%~90%, vacuumize until the vacuum degree in the container is below 0.01 MPa, and introduce argon to avoid oxidation of the alloy powder during the powder mixing process; introduce circulating cooling water to reduce the temperature of the powder during powder mixing; set the powder mixing procedure, the mixing is divided into two stages, the first stage has a mixing acceleration of 10~20 g and a mixing time of 5~15 min, the second stage has a mixing acceleration of 80~90 g and a mixing time of 40~60 min; after the mixing is completed, wait until the powder cools down to room temperature, then take out the powder.
[0015] A printed part, which is manufactured using the above-mentioned alloy powder.
[0016] The beneficial effects of the present invention are as follows: 1. The present invention provides an oxide dispersion strengthened alloy powder suitable for additive manufacturing (especially laser powder bed fusion technology). The alloy powder not only has good sphericity, high fluidity and appropriate particle size distribution to ensure the smooth progress of the printing process, its composition design can form a dense component with uniform nano-oxide dispersed phases after printing, more importantly, the composition of the powder can be changed at lower cost and in shorter time.
[0017] 2. The alloy powder preparation method of the present invention can achieve uniform and firm coating of nano-oxides on the surface of metal powder, avoiding oxide agglomeration or segregation in subsequent additive manufacturing processes, thereby ensuring the uniformity and reliability of the final part performance.
[0018] 3. The printed parts made from the alloy powder of this invention exhibit excellent mechanical properties, including high strength and high creep resistance, even at high temperatures (e.g., above 900°C), meeting the stringent requirements of high-end high-temperature components in aerospace, energy, and power industries. The alloy powder of this invention combines good formability with excellent high-temperature mechanical properties, and provides a preparation method capable of achieving uniform coating of nano-oxides. The high-performance printed parts made from this powder have significant practical importance and application value for overcoming manufacturing bottlenecks in high-end high-temperature components and promoting technological progress in aerospace and energy fields. This invention provides an oxide dispersion-strengthened cobalt-chromium-nickel alloy powder suitable for additive manufacturing. The core feature of this alloy powder lies in its unique composition and structure. By adding oxide powder to a pre-alloyed powder, the high-temperature performance of the alloy is improved. An appropriate amount of Mo can improve the wettability of the melt to rare earth oxides, reduce interfacial energy, and thus inhibit the agglomeration and segregation of rare earth oxide particles, resulting in a uniformly dispersed state within the matrix. These uniformly distributed rare earth oxide particles can significantly improve the room-temperature yield strength and tensile strength of the alloy by strongly pinning dislocations, combined with the solid solution strengthening effect of Mo itself. More importantly, at high temperatures, the uniformly dispersed rare earth oxide particles, under the synergistic effect of Mo, can effectively suppress dislocation movement and grain boundary slip, allowing the alloy to maintain high tensile strength and good plasticity at high temperatures, thereby achieving simultaneous optimization of room-temperature and high-temperature mechanical properties. However, the amount of Mo added is crucial; too little will lead to poor dispersion and weak strengthening effect; too much may cause rare earth oxides to enrich and coarsen along grain boundaries, thus reducing the alloy's performance.
[0019] The overall alloy element composition of this invention is limited, and the rare earth oxide is one or more combinations of oxides of yttrium, lanthanum, cerium, neodymium, gadolinium, and erbium, with yttrium oxide being preferred. The rare earth oxide powder preferably has a particle size of 100 to 200 nanometers. This nanoscale oxide can act as effective pinning points, hindering dislocation movement and grain boundary migration, thereby significantly improving the high-temperature performance of the material.
[0020] In this invention, the molybdenum powder has a particle size of 1 to 5 micrometers. Adding this particle size significantly promotes the uniform dispersion of oxide particles in the alloy matrix. The addition of this Mo powder not only improves the wettability of the melt on the oxide particles and inhibits particle agglomeration, but also "locks" the oxide particles within the grains by promoting the formation of fine equiaxed crystals, thus achieving an ideal dispersed distribution. Furthermore, Mo can further alloy the matrix, enhancing the material's strength through a solid solution strengthening mechanism. Mo atoms entering the matrix lattice cause lattice distortion, increasing the resistance to dislocation movement, thereby improving the alloy's yield strength and tensile strength.
[0021] The alloy powder of this invention forms a core-shell structure, wherein a pre-alloyed powder is the core, and elemental metal powder and oxide powder are uniformly coated on the surface of the pre-alloyed powder through a resonant mixing process to form a complete coating layer. This structure ensures that during subsequent laser melting, the elemental metal can be uniformly melted into the base alloy to form an ideal solid solution strengthening effect, and the oxide can be uniformly dispersed in the molten pool to form an ideal dispersion strengthening effect.
[0022] The method for preparing the alloy powder of the present invention.
[0023] The mixing process is preferably carried out under an argon atmosphere to avoid oxidation of the powder during high-energy mixing. Simultaneously, circulating cooling water is used to cool the powder system and inhibit powder agglomeration. A two-step mixing program is designed to be completed in two stages. Initially, a lower acceleration helps to better disperse the powder and prevents undispersed powder from agglomerating under higher acceleration. In the second stage, a high acceleration is used to ensure that the elemental metal powder and nano-oxide powder firmly coat the surface of the pre-alloyed powder. Too short a time will result in incomplete coating of the elemental metal powder and nano-oxide powder on the pre-alloyed powder surface, while too long a time will cause some of the already coated powder to detach under shear force.
[0024] The alloy powder of this invention produces printed parts through additive manufacturing. The printed parts have uniform composition and uniformly distributed nano-oxide dispersion phases inside, exhibiting excellent room temperature and high temperature performance. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1This is a schematic diagram of the quasi-static tensile stress-strain curves of the oxide dispersion strengthened high-entropy alloys prepared in Examples 1, 2 and 3 of the present invention at room temperature. Figure 2 This is a schematic diagram of the quasi-static tensile stress-strain curves of the oxide dispersion-strengthened high-entropy alloys prepared in Examples 1, 2 and 3 of this invention at 900°C. Figure 3 This is a schematic diagram of the X-ray diffraction patterns of the oxide dispersion-strengthened high-entropy alloys prepared in Examples 1, 2 and 3 of this invention; Figure 4 This is a schematic diagram of a SEM image of the oxide dispersion-strengthened high-entropy alloy prepared in Example 2 of the present invention. Figure 5 This is a schematic diagram of a SEM image of the oxide dispersion-strengthened high-entropy alloy prepared in Example 3 of the present invention. Detailed Implementation
[0027] To better understand the technical solution of the present invention, the embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0028] Example 1
[0029] A cobalt-chromium-nickel alloy powder for additive manufacturing, the alloy powder being composed of pre-alloyed powder, elemental metallic powder, and oxide powder, wherein the elemental composition of the alloy powder is Co. a Cr b Ni c Mo d W e Re f Al g C h (RE2O3) i The alloy powder contains rare earth elements (RE) and oxide powder (RE2O3). The mass percentages of each element or component in the alloy powder are as follows: 10 ≤ a ≤ 50 wt%, 10 < b ≤ 50 wt%, 10 < c ≤ 50 wt%, 0 < d ≤ 5 wt%, 0 < e ≤ 5 wt%, 0 < f ≤ 5 wt%, 0 < g ≤ 2 wt%, 0 < h ≤ 2 wt%, 0 < i ≤ 2 wt%, and a + b + c + d + e + f + g + h + i = 100 wt%. The metallic elemental powder is Mo elemental powder.
[0030] Furthermore, the chemical formula of the pre-alloyed powder is Co. a Cr b Ni c We Re f Al g C h The atomic ratios of the components in the formula are: 10≤a≤50 at%, 10<b≤50 at%, 10<c≤50 at%, 0<e≤5 at%, 0<f≤5at%, 0<g≤2 at%, 0<h≤2 at%, and a+b+c+e+f+g+h=100 at%.
[0031] Furthermore, the particle size of the metal elemental powder is 1~5 μm.
[0032] Furthermore, the oxide powder is at least one of yttrium oxide, lanthanum oxide, cerium oxide, and neodymium oxide, and the particle size of the oxide powder is 100~200 nm.
[0033] Furthermore, the chemical formula of the pre-alloyed powder is Co. 32.7 Cr 32.2 Ni 32.3 W1Re 0.5 Al1C 0.3 .
[0034] A method for preparing the above-mentioned alloy powder, the method comprising the following steps: S1) Weigh the pre-alloyed powder raw materials according to the designed proportions, convert the atomic percentages of each component of the pre-alloyed powder raw materials into mass percentages, and weigh the raw materials according to the mass percentages. The purity of the raw materials is ≥99.9 wt.%. S2) The raw materials weighed in S1) are mixed and then subjected to vacuum induction melting to obtain alloy ingots; S3) The alloy ingot described in S2) is subjected to gas atomization treatment to obtain pre-alloyed powder; S4) The pre-alloyed powder described in S3) is sieved to obtain pre-alloyed powder with a size of 15~53 μm; S5) Weigh the required mass of elemental metal powder, oxide powder and pre-alloyed powder obtained in S4) according to the design ratio, and dry them. Specific drying process: Place the elemental metal powder, oxide powder, and pre-alloyed powder into a vacuum drying oven, open the vacuum valve, and evacuate until the vacuum level inside the chamber reaches below 0.01 MPa, then close the vacuum valve. Set the heating program for the drying oven, with a temperature of 80℃~120℃ and a time of 5~10 hours. When the heating time is reached, allow the chamber to cool naturally to room temperature. Open the vent of the drying oven, and when the air pressure inside the chamber returns to atmospheric pressure, open the drying oven and remove the powder. S6) Subject the dried elemental metal powder, oxide powder and pre-alloyed powder to resonant powder mixing treatment to obtain the alloy powder suitable for additive manufacturing.
[0035] Further, the specific process of the vacuum induction melting comprises: placing the raw materials in a crucible, evacuating the melting chamber to a low vacuum, supplying power at low power to preheat the furnace charge, then evacuating the melting chamber to a high vacuum, supplying power at high power to maintain the melting temperature at 1550~1600°C, applying electromagnetic stirring to promote composition homogenization, and pouring after uniform stirring.
[0036] Further, the specific process of the gas atomization treatment comprises: heating the alloy ingot to a molten state under the protection of an argon atmosphere, obtaining fine droplets through a supersonic argon flow nozzle, with an atomization pressure of 3~9 MPa. During the falling process of the atomized droplets in the atomization tower, the droplets shrink into spheres under the action of surface tension, and rapidly cool and solidify into solid pre-alloyed powder.
[0037] Further, the specific process of the resonant powder mixing treatment comprises: placing the elemental metal powder, oxide powder and pre-alloyed powder into the matching container of the powder mixer, wherein the powder filling ratio in the container reaches 80%~90%, evacuating the container until the vacuum degree in the container is below 0.01 MPa, and introducing argon to avoid oxidation of the alloy powder during the powder mixing process; introducing circulating cooling water to reduce the temperature of the powder during powder mixing; setting the powder mixing procedure, the mixing is divided into two stages, the first stage has a mixing acceleration of 10~20 g and a mixing time of 5~15 min, the second stage has a mixing acceleration of 80~90 g and a mixing time of 40~60 min; after the mixing is completed, wait until the powder cools to room temperature, then take out the powder.
[0038] A printed part, which is manufactured using the above-mentioned alloy powder.
[0039] An oxide dispersion strengthened high-entropy alloy with both high strength and high plasticity at room temperature and high temperature, which is prepared from the cobalt-chromium-nickel series alloy powder. The matrix composition (atomic ratio) of the pre-alloyed powder is: Ni 32.3 Co 32.7 Cr 32.2 W1Al1Re 0.5 C 0.3 , the elemental metal is elemental Mo with a content of 1 wt.%, the oxide is Y₂O₃ with a content of 1 wt.%, and the sum of the mass percentages of the matrix, the elemental metal and the oxide is 100 wt%. The room temperature yield strength of the alloy is 656 MPa, the tensile strength is 908 MPa, the tensile plasticity is 28%, the tensile strength at 900°C is 269.5 MPa, and the tensile plasticity is 16%. The prepared alloy is mainly composed of FCC phase, and the oxide particles are uniformly distributed in the matrix.
[0040] Example 2
[0041] An oxide dispersion-strengthened high-entropy alloy, prepared from the aforementioned cobalt-chromium-nickel alloy powder, exhibiting high strength and high plasticity at both room temperature and high temperature, has a pre-alloyed powder matrix composition (atomic ratio) of: Ni 32.3 Co 32.7 Cr 32.2 W1Al1Re 0.5 C 0.3 The metallic element is Mo, with a content of 2 wt.%, and the oxide is Y₂O₃, with a content of 1 wt.%, and the sum of the mass percentages of the matrix and oxide is 100 wt%. The alloy has a room temperature yield strength of 705 MPa, a tensile strength of 963 MPa, and a tensile plasticity of 34.5%. At 900℃, the tensile strength is 276.3 MPa, and the tensile plasticity is 28%. The prepared alloy is mainly composed of the FCC phase, such as... Figure 4 As shown, oxide particles are uniformly distributed in the matrix.
[0042] Example 3
[0043] An oxide dispersion-strengthened high-entropy alloy, prepared from the aforementioned cobalt-chromium-nickel alloy powder, exhibiting high strength and high plasticity at both room temperature and high temperature, has a pre-alloyed powder matrix composition (atomic ratio) of: Ni 32.3 Co 32.7 Cr 32.2 W1Al1Re 0.5 C 0.3 The alloy contains elemental Mo (Mo) at a content of 3 wt.%, and Y₂O₃ (Y₂O₃) at a content of 1 wt.%, with a total mass percentage of 100 wt% for both the matrix and oxide. The alloy exhibits a room temperature yield strength of 765 MPa, a tensile strength of 964 MPa, and a tensile plasticity of 14.3%. At 900℃, the tensile strength is 282 MPa, and the tensile plasticity is 18%. The prepared alloy is primarily composed of the FCC phase, such as... Figure 5 As shown, micron-sized Y2O3 aggregates exist on the substrate surface.
[0044] Example 4 (Comparative Example 1) An oxide dispersion-strengthened high-entropy alloy, wherein the pre-alloyed powder matrix composition (atomic ratio) is: Ni 32.3 Co 32.7 Cr 32.2 W1Al1Re 0.5 C 0.3The oxide composition is Y2O3, with a content of 1 wt.%, and the sum of the mass percentages of the matrix and oxide is 100 wt%. The alloy has a room temperature yield strength of 641 MPa, a tensile strength of 874 MPa, and a tensile plasticity of 22%. At 900℃, the tensile strength is 260 MPa, and the tensile plasticity is 24%. The prepared alloy is mainly composed of the FCC phase.
[0045] The oxide dispersion-strengthened high-entropy alloys prepared from cobalt-chromium-nickel alloy powders in Examples 1, 2, and 3 exhibit both high strength and high plasticity at room temperature and high temperature. These high-entropy alloys have a face-centered cubic structure with dispersed nanoscale rare earth oxides in the matrix. Their room temperature yield strength is 656-765 MPa, tensile strength is 908-964 MPa, and elongation at break is 14.3%-34.5%. At 900℃, their tensile strength is 269.5-282 MPa, and elongation at break is 16-28%. Compared to the high-entropy alloy in Example 4 (Comparative Example 1), the high-entropy alloy prepared by the method of this invention shows significantly better yield strength and tensile strength at room temperature and tensile strength at 900℃. This demonstrates that the addition of elemental Mo significantly improves the performance of the high-entropy alloy. Furthermore, actual research revealed that when the pre-alloyed powder matrix composition (atomic ratio) is Co... 32.7 Cr 32.2 Ni 32.3 W1Re 0.5 Al1C 0.3 When the high-entropy alloy prepared by the method of the present invention is prepared, its yield strength and tensile strength at room temperature and tensile strength at 900℃ all show better optimization effects.
[0046] Example 5
[0047] An oxide dispersion-strengthened cobalt-chromium-nickel alloy powder suitable for additive manufacturing, with an overall alloy element composition of Co. a Cr b Ni c Mo d W e Re f Al g C h (RE2O3) i The alloy is composed of rare earth elements (RE) and rare earth oxides (RE₂O₃). The mass percentages of each element / component are: 10 ≤ a ≤ 50 wt%, 10 < b ≤ 50 wt%, 10 < c ≤ 50 wt%, 0 < d ≤ 5 wt%, 0 < e ≤ 5 wt%, 0 < f ≤ 5 wt%, 0 < g ≤ 2 wt%, 0 < h ≤ 2 wt%, 0 < i ≤ 2 wt%, and a + b + c + d + e + f + g + h + i = 100 wt%. The chemical formula of this pre-alloyed powder matrix alloy is Co. aCr b Ni c W e Re f Al g C h The atomic ratios of each component are: 10 ≤ a ≤ 50 at%, 10 < b ≤ 50 at%, 10 < c ≤ 50 at%, 0 < e ≤ 5 at%, 0 < f ≤ 5 at%, 0 < g ≤ 2 at%, 0 < h ≤ 2 at%, and a + b + c + e + f + g + h = 100 at%.
[0048] A method for oxide dispersion-strengthened cobalt-chromium-nickel alloy powder suitable for additive manufacturing, the method specifically includes the following steps: S1) According to the design ratio, convert the atomic percentage of each raw material into the required mass percentage of each element, and weigh the corresponding mass of each raw material; each raw material is a metallic elemental raw material, a non-metallic elemental raw material, and an oxide raw material with a purity ≥99.9 wt.%; S2) The raw materials weighed in S1) are mixed and then subjected to vacuum induction melting to obtain alloy ingots; The specific process of vacuum induction melting: Place the raw materials in a crucible, evacuate the melting chamber to a low vacuum, preheat the furnace charge with low power, then evacuate the melting chamber to a high vacuum, and maintain the melting temperature at 1550~1600℃ with high power. Apply electromagnetic stirring to promote homogenization of the composition. After stirring evenly, pour the mixture. S3) The S2) alloy ingot is subjected to gas atomization treatment to obtain pre-alloyed powder; the specific process of gas atomization treatment is as follows: Under the protection of argon atmosphere, the cast alloy is heated to the molten state and obtained into tiny droplets through a supersonic argon gas nozzle. The atomization pressure is 3~9 MPa. During the falling process in the atomization tower, the atomized droplets shrink into spherical shapes due to surface tension and rapidly cool and solidify into solid pre-alloyed powder.
[0049] S4) The pre-alloyed powder of S3) is sieved to obtain pre-alloyed powder with a size of 15~53 μm; S5) Weigh the required mass of elemental metal powder, oxide powder and pre-alloyed powder obtained in S4) according to the design ratio, and dry them. Specific drying process: Place the elemental metal powder, oxide powder, and pre-alloyed powder into a vacuum drying oven, open the vacuum valve, and evacuate until the vacuum level inside the chamber reaches below 0.01 MPa, then close the vacuum valve. Set the heating program for the drying oven, with a temperature of 80℃~120℃ and a time of 5~10 hours. When the heating time is reached, allow the chamber to cool naturally to room temperature. Open the vent of the drying oven, and when the air pressure inside the chamber returns to atmospheric pressure, open the drying oven and remove the powder. S6) The dried metal powder and oxide powder are subjected to resonant mixing treatment to obtain alloy powder suitable for additive manufacturing; Specific process of resonance powder mixing treatment: Both metal powder and oxide powder are placed into the container of the powder mixer, with the powder-to-filling ratio in the container reaching 80%~90%. The container is evacuated to a vacuum level below 0.01 MPa. Argon gas is introduced to prevent the alloy powder from oxidizing during the mixing process. Circulating cooling water is introduced to lower the powder temperature during mixing. The mixing program is set, with mixing in two stages: the first stage has a mixing acceleration of 10~20 g and a mixing time of 5~15 min, and the second stage has a mixing acceleration of 80~90 g and a mixing time of 40~60 min. After mixing, the powder is allowed to cool to room temperature before being removed.
[0050] Microstructure analysis: The microstructure of the printed lightweight high-temperature alloy was observed using a Supra 55 field emission scanning electron microscope (Zeiss, Germany); samples of 10 × 3 × 1.3 mm were cut using wire electrical discharge machining. 3 Thin sheet samples, sequentially using 240 # 600 # 1000 # and 2000 # Mechanical polishing was performed using sandpaper, followed by electrochemical polishing with a 10% perchloric acid + 90% anhydrous ethanol (volume fraction) electrolyte. The polished sample was then placed in deionized water for thorough dilution to remove residual electrolyte, and then placed in anhydrous ethanol for ultrasonic cleaning. After the sample was fully dried, it was observed under an electron microscope. Room temperature quasi-static tensile mechanical property testing: Room temperature tensile mechanical property tests were conducted using a CMT 4105 electronic universal testing machine at a strain rate of 1 × 10⁻⁶. -3 s -1 The sample was machined using an electrical discharge wire cutting machine to a gauge length of 5 × 15 × 1.3 mm. 3 Tensile tests were performed on dog bone-shaped plate specimens, with at least three samples selected for each alloy composition to ensure the repeatability of the test. High-temperature quasi-static tensile mechanical property testing: High-temperature tensile mechanical property tests were conducted using a LE 5105 electronic universal testing machine at a strain rate of 1 × 10⁻⁶. -3 s -1 The sample was machined using an electrical discharge wire cutting machine to a gauge length of 4 × 15 × 1.5 mm. 3 Tensile tests were performed on dog bone-shaped plate specimens, with at least three samples selected for each alloy composition to ensure the repeatability of the test. The high-entropy alloy prepared by the method has a face-centered cubic structure with nanoscale rare earth oxides dispersed in the matrix. The room temperature yield strength is 656-765 MPa, the tensile strength is 908-964 MPa, and the elongation at break is 14.3%-34.5%. The tensile strength at 900℃ is 269.5-282 MPa, and the elongation at break is 16-28%.
[0051] The embodiments of the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A cobalt-chromium-nickel alloy powder for additive manufacturing, characterized in that, The alloy powder is composed of pre-alloyed powder, elemental metal powder, and oxide powder, and the elemental composition of the alloy powder is Co. a Cr b Ni c Mo d W e Re f Al g C h (RE2O3) i The alloy powder contains rare earth elements (RE) and oxide powder (RE2O3). The mass percentages of each element or component in the alloy powder are as follows: 10 ≤ a ≤ 50 wt%, 10 < b ≤ 50 wt%, 10 < c ≤ 50 wt%, 0 < d ≤ 5 wt%, 0 < e ≤ 5 wt%, 0 < f ≤ 5 wt%, 0 < g ≤ 2 wt%, 0 < h ≤ 2 wt%, 0 < i ≤ 2 wt%, and a + b + c + d + e + f + g + h + i = 100 wt%. The metallic elemental powder is Mo elemental powder.
2. The alloy powder according to claim 1, characterized in that, The chemical formula of the pre-alloyed powder is Co. a Cr b Ni c W e Re f Al g C h The atomic ratios of the components in the formula are: 10≤a≤50 at%, 10<b≤50 at%, 10<c≤50 at%, 0<e≤5 at%, 0<f≤5at%, 0<g≤2 at%, 0<h≤2 at%, and a+b+c+e+f+g+h=100at%.
3. The alloy powder according to claim 2, characterized in that, The particle size of the elemental metal powder is 1 to 5 μm.
4. The alloy powder according to claim 3, characterized in that, The oxide powder is at least one of yttrium oxide, lanthanum oxide, cerium oxide and neodymium oxide, and the particle size of the oxide powder is 100 to 200 nm.
5. The alloy powder according to claim 4, characterized in that, The chemical formula of the pre-alloyed powder is Co. 32.7 Cr 32.2 Ni 32.3 W1Re 0.5 Al1C 0.3 .
6. A method for preparing the alloy powder as described in any one of claims 1-5, characterized in that, The method comprises the following steps: S1) Weigh the pre-alloy powder raw materials according to the designed ratio, convert the atomic percentage of each component of the pre-alloy powder raw materials into mass percentage, and weigh the raw materials according to the mass percentage, wherein the purity of the raw materials is ≥99.9 wt.%; S2) Mix the raw materials weighed in S1 and perform vacuum induction smelting treatment to obtain an alloy ingot; S3) Perform gas atomization treatment on the alloy ingot described in S2 to obtain pre-alloy powder; S4) Perform sieving treatment on the pre-alloy powder described in S3 to obtain pre-alloy powder with a size of 15 to 53 μm; S5) According to the designed ratio, weigh the required mass of the elemental metal powder, the oxide powder and the pre-alloy powder obtained in S4, and perform drying treatment; S6) Subject the dried elemental metal powder, oxide powder and pre-alloy powder to resonant powder mixing treatment to obtain the alloy powder suitable for additive manufacturing.
7. The preparation method according to claim 6, characterized in that, The specific process of the vacuum induction smelting comprises: placing the raw materials in a crucible, pumping the smelting chamber to a low vacuum, supplying power at low power to preheat the furnace charge, then pumping the smelting chamber to a high vacuum, and supplying power at high power to maintain the smelting temperature at 1550 to 1600°C.
8. The preparation method according to claim 7, characterized in that, The specific process of the gas atomization treatment comprises: heating the alloy ingot to a molten state under the protection of an argon atmosphere, obtaining fine droplets through a supersonic argon flow nozzle, wherein the atomization pressure is 3 to 9 MPa.
9. The preparation method according to claim 8, characterized in that, The specific process of the resonant powder mixing treatment comprises: placing the elemental metal powder, the oxide powder and the pre-alloy powder into a matching container of a powder mixer, evacuating to a vacuum degree of 0.01 MPa or less in the container, and introducing argon to prevent the alloy powder from being oxidized during the powder mixing process; introducing circulating cooling water to reduce the temperature of the powder during powder mixing; the mixing is divided into two stages, the mixing acceleration in the first stage is 10 to 20 g with a mixing time of 5 to 15 min, and the mixing acceleration in the second stage is 80 to 90 g with a mixing time of 40 to 60 min.
10. A printed document, characterized in that, The printed part is manufactured by using the alloy powder according to any one of claims 1 to 5.
